2023
DOI: 10.1093/mtomcs/mfad008
|View full text |Cite
|
Sign up to set email alerts
|

Chryseochelins—structural characterization of novel citrate-based siderophores produced by plant protecting Chryseobacterium spp.

Abstract: Bacteria secrete siderophores whose function is to acquire iron. In recent years, the siderophores of several Chryseobacterium species were shown to promote the health and growth of various plants such as tomato or rice. However, the chemical nature of Chryseobacterium siderophores remained unexplored despite great interest. In this work, we present the purification and structure elucidation by NMR and MS/MS of chryseochelin A, a novel citrate-based siderophore secreted by three Chryseobacterium strains involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In regards to metallophore activity, when looking at the genome one can see ES2 T possess all the required genes for siderophore production and activity, specifically the mixed-type, citrate-hydroxamate based, aerobactin [46], similar to other Chryseobacterium , which also have mixed-type siderophores [6]. Specific genes for the chelation of other metals, such as the rare earth elements, have not been identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In regards to metallophore activity, when looking at the genome one can see ES2 T possess all the required genes for siderophore production and activity, specifically the mixed-type, citrate-hydroxamate based, aerobactin [46], similar to other Chryseobacterium , which also have mixed-type siderophores [6]. Specific genes for the chelation of other metals, such as the rare earth elements, have not been identified.…”
Section: Resultsmentioning
confidence: 99%
“…C138 siderophores to tomato plants also demonstrated a sufficient supply of iron for plant growth thus suggesting this genus’ dual ability of not only sequestering iron from the environment, but then resupplying to agriculture as necessary [5]. Other Chryseobacterium species possess siderophore activity [6, 7], suggesting that they may also be of use in similar fashion to C. herbae and Chryseobacterium sp. C138.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that siderophore-mediated interactions play a key role in this process 44,52 . For example, it was shown that plant-beneficial Chryseobacterium strains use their siderophores to suppress the plant-pathogen Ralstonia solanacearum 53 . The approach has recently been extended to human pathogens, which were found to be suppressed by exclusive siderophores from environmental Pseudomomnas spp.…”
Section: Discussionmentioning
confidence: 99%
“…Digitalized natural product databases do not offer publicly accessible and searchable instances of "siderophore" and only contain a fraction of currently known siderophores. Previous case-by-case research on siderophores reported their siderophore discoveries by images of the structural formula [10][11][12][13][14] , as do previous reviews and the siderophore base. Although tools are available for converting chemical structure images to SMILES, their accuracy is limited [23][24][25] .…”
Section: Introductionmentioning
confidence: 86%
“…However, the database was last updated in 2013 and is no longer maintained. Moreover, new siderophore molecules (12)(13)(14)(15), and even new siderophore functional group types (diazeniumdiolate and 2-nitrosophenol) (16)(17)(18)(19), are constantly being discovered in various microorganisms. (3) Information regarding these siderophores is currently dispersed across various publications and needs to be systematically recorded.…”
Section: Introductionmentioning
confidence: 99%